A Robust Operation Method with Advanced Adiabatic Compressed Air Energy Storage for Integrated Energy System under Failure Conditions - Rong Xie; Weihuang Liu; Muyan Chen; Yanjun Shi (Machines, 2022)
Integrated energy system (IES) is an important direction for the future development of the energy industry, and the stable operation of the IES can ensure heat and power supply. This study established an integrated system composed of an IES and advanced adiabatic compressed air energy storage (AA-CAES) to guarantee the robust operation of the IES under failure conditions. Firstly, a robust operation method using the AA-CAES is formulated to ensure the stable operation of the IES. The method splits the energy release process of the AA-CAES into two parts: a heat-ensuring part and a power-ensuring part. The heat-ensuring part uses the high-temp tank to maintain the balance of the heat subnet of the IES, and the power-ensuring part uses the air turbine of the first stage to maintain the balance of the power subnet. Moreover, another operation method using a spare gas boiler is formulated to compare the income of the IES with two different methods under failure conditions. The results showed that the AA-CAES could guarantee the balance of heat subnet and power subnet under steady conditions, and the dynamic operation income of the IES with the AA-CAES method was a bit higher than the income of the IES with the spare gas boiler method.